The antlered ship - Slater, Dashka; Fan, Eric; Fan, Terry (New York : Beach Lane Books, 2017)
An inquisitive fox named Marco and a bored flock of pigeons join the crew of deer Captain Sylvia, setting sail in her antlered ship in search of a wonderful island and finding friendship on the way.
Keywords: Friendship -- Fiction; Ocean travel -- Fiction; Foxes -- Fiction; Deer -- Fiction; Pigeons -- Fiction; Sea adventure fiction